1994
DOI: 10.2307/1131511
|View full text |Cite|
|
Sign up to set email alerts
|

The Influence of Temperament and Mothering on Attachment and Exploration: An Experimental Manipulation of Sensitive Responsiveness among Lower-Class Mothers with Irritable Infants

Abstract: 6-month-old infants selected on irritability shortly after birth and their mothers were randomly assigned to 2 intervention and 2 control groups to test the hypothesis that enhancing maternal sensitive responsiveness will improve quality of mother-infant interaction, infant exploration, and attachment. The intervention lasted 3 months and ended when the child was 9 months of age. When infants were 9 months of age, intervention group mothers were significantly more responsive, stimulating, visually attentive, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
239
1
14

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(274 citation statements)
references
References 24 publications
20
239
1
14
Order By: Relevance
“…40 The nature and extent of overlap between attachment and temperament have been addressed by both theoretical and empirical studies. 41 There is empirical support for the contribution of both parenting behavior 42,43 and early temperament (eg, negative emotionality 44,45 or reactivity 46 ) to insecure and disorganized attachment, but the correlations are only small to moderate. Also, it is not clear what the causal relationships are among individual variations of temperament, parental behavior, and attachment quality.…”
Section: Discussionmentioning
confidence: 99%
“…40 The nature and extent of overlap between attachment and temperament have been addressed by both theoretical and empirical studies. 41 There is empirical support for the contribution of both parenting behavior 42,43 and early temperament (eg, negative emotionality 44,45 or reactivity 46 ) to insecure and disorganized attachment, but the correlations are only small to moderate. Also, it is not clear what the causal relationships are among individual variations of temperament, parental behavior, and attachment quality.…”
Section: Discussionmentioning
confidence: 99%
“…To test the differential susceptibility hypothesis, we chose an a priori split that was meant to separate the most reactive children from the children with moderate or low reactivity. In Van den Boom's (1994) intervention study among lowerclass mothers and their irritable infants, 17% of 6-month-old infants were found to be irritable. This is congruent with the borderline/clinical cutoff for children scoring above the 82.7th percentile as used for the Child Behavior Checklist (CBCL; Achenbach, 1991).…”
Section: Methodsmentioning
confidence: 98%
“…Studies conducted since Crockenberg's review continue to vary on a number of dimensions including demographic characteristics, whether the sample is selected on the basis of extreme temperament, and whether potential moderators such as social support, stress, marital satisfaction, or maternal depression are assessed. This research also indicated inconsistent relations between maternal behavior and infant temperament (Mangelsdorf et al, 1990;Owens, Shaw, & Vondra, 1998;Pauli-Pott, Mertesacker, Bade, Bauer, & Beckmann, 2000;Seifer et al, 1996;van den Boom, 1994;van den Boom & Hoeksma, 1994). Thompson (1998) noted that more research is needed to understand the complex transactional relations that likely exist between infant and parent characteristics.…”
mentioning
confidence: 90%
“…In addition, we identified these infants from a larger community sample to generate a group of infants who were clearly different from other, less easily frustrated infants. Our assumption was that associations between maternal behavior and infant frustration would be more likely in such a sample (Crockenberg, 1986;van den Boom, 1994;van den Boom & Hoeksma, 1994). Finally, we collected maternal reports of parenting stress, marital adjustment, and psychopathology.…”
mentioning
confidence: 99%